The hazardous consequences of rising air pollution on perinatal outcomes - Ahmed Kamal Siddiqi (Journal of the Pakistan Medical Association, 2022)
To the editor: Adverse birth results, for example, preterm birth (PTB: under 37 weeks of pregnancy) and low birth weight (LBW: under 2.5kg) have been connected to a rise in neonatal bleakness and mortality with possible formative disabilities and probability of various infections in adulthood (1). All around the world, preterm birth is the central reason for neonatal mortality, adding to (35%) of world’s neonatal mortality. Additionally, it’s the cause of lifetime disabilities and many chronic diseases. Annually 15 million pre-term children are conceived, around 1 million die due to complications (2). Over 60% of preterm births happen in South Asia and Sub-Saharan Africa. On the other hand, low birthweight children experience development impediments and intellectual developments in later life (2). Hazard factors connected to these adverse birth results incorporate maternal age, drinking, smoking, infection during pregnancy, repeated pregnancies and so forth (1). Nonetheless, there is developing proof that air contamination assumes a critical part in event of ominous birth results (1). As of late, another review links air contamination to 6 million pre-term births and 3 million underweight newborn children in 2019 because of air contamination. The review shows that indoor air contamination, principally from cooking ovens represents 2/3rd of these perinatal results (3). Air holding fine particulate matter (PM) of 2.5 micrometrs or less is related to antagonistic neonatal results. Persistent PM2.5 exposure induces conceptive toxicity refereed by placental DNA methylation and maternal inflammatory reactions, proposing a connection between PM2.5 exposure and preterm birth hazard (4). The particles have likewise been related to pregnancy-instigated hypertensive problems, expanding the danger of development impediment and preterm birth (3). As indicated by this new study, over 92% of the worldwide population lives in regions where the air quality is underneath the limits as far as possible set by World Health Organization (WHO), and around 49% are presented to similarly undeniable degrees of indoor air contamination (3). The study also discovered that air contamination is generally widespread in South Asia and sub-Saharan Africa, two regions with universally the most noteworthy preterm births. Study’s authors conclude that decreasing the air contamination in these two regions could essentially diminish the frequency of preterm birth and low birth weight by 78% worldwide (3). —Continue